Pengaruh Penerapan Model Pembelajaran Make A Match Terhadap Minat Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas XI SMA Negeri 1 Pagaran Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024. - Menta Uli Purba; Albiner Siagian; Simion D. Harianja; Johari Manik; Taripar A. Samosir (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
Learning models greatly determine the success of learning, including students' interest in learning. This research aims to determine the effect of implementing the Make A Match learning model on interest in studying Christian Religious Education and Characteristics of class XI students at SMA Negeri 1 Pagaran, North Tapanuli Regency for the 2023/2024 academic year. The method used in this research is a quantitative method, a type of pre-experimental approach with a "One Group Pretest-Posttest Design" design. The population was all 200 students of class XI SMA Negeri 1 Pagaran who were Christians and a sample of 35 people was determined, namely class Data analysis uses the paired sample t-test formula. After conducting a pretest and posttest on the sample, the results of data analysis showed that the tcount > ttable value was 21.333 > 1.691. So H1 is accepted and H0 is rejected. Based on the results of this research, it is known that by using the Make A Match learning model students' interest in learning can increase, this can be seen from the average score of 87.74 to 103 with a difference of 15.26. Thus, the researchers concluded that there was a positive and significant influence of implementing the Make A Match learning model on interest in studying Christian Religious Education and Character in Class